The Intra- and Inter-Rater Reliability of a Hip Rotation Range-of-Motion Measurement Using a Smartphone Application in Academy Football (Soccer) Players - Paul Spork; James O'Brien; Morris Sepoetro; Maximilian Plachel; Thomas Stöggl (MDPI AG, 2021)
The clinical assessment of hip rotation range-of-motion (ROM) is important for managing hip and groin injuries in footballers. Previously published reliability studies on hip ROM have employed protocols that are difficult to replicate under everyday clinical conditions. This single trial, intra- and inter-rater reliability study included 41 male academy football (soccer) players, aged 14-15 years, from one European football academy. Passive hip internal rotation (IR) and external rotation (ER) ROM were measured in supine with hip and knee flexed to 90°. The ROM was determined using a smartphone application, with the smartphone attached to the lower leg. The tests were performed on two separate occasions, one week apart, by two different physiotherapists and on both sides (left and right hips). Reliability was evaluated using Intra-Class Correlation Coefficients (ICCs) and Minimal Detectable Change (MDC). Hip IR and ER ROM displayed moderate to good intra-rater agreement (ICCs 0.54-0.75), with MDCs ranging from 10.9° to 16.4°. Inter-rater reliability displayed poor to moderate reliability (ICCs 0.33-0.75), with MDCs ranging from 11.7° to 16.5°. A hip rotation ROM test using a smartphone application and a protocol closely reflecting everyday clinical conditions displayed moderate to good intra-rater reliability and poor to moderate inter-rater reliability. Due to the high MDCs, the practical applicability of this test procedure is limited and further refinement is necessary.